Communication rehabilitation in sub-Saharan Africa: The role of speech and language therapists - Wylie, Karen; McAllister, Lindy; Davidson, Bronwyn; Marshall, Julie (AOSIS, 2018)
Background: Workforce factors present a significant barrier to the development of rehabilitation services for people with communication disabilities in sub-Saharan Africa (SSA). Exploring how the work of speech and language therapists (SLTs) in the region is organised and delivered can provide insight into existing services, areas for future workforce development and improved rehabilitation access for people with communication disability.Objectives: This paper describes the employment and service provision patterns and work roles of a sample of SLTs in SSA.Method: A broad, purpose-designed, mixed-methods survey was designed to collect data from SLTs living in Anglophone countries of SSA. Descriptive statistics and qualitative content analysis were undertaken. This paper reports on a subset of data from the wider survey.Results: A description of the employment and work roles of the 33 respondents to the survey and characteristics of their service users is presented. SLTs were commonly employed within private and not-for-profit sectors and frequently worked in temporary jobs. SLTs engaged in a range of work roles, including capacity building and training others. Services were provided by SLTs across age ranges, health conditions and settings, with paediatric, urban services commonly reported. Costs for service users and urban-centred services give indications of barriers to service access.Conclusion: Knowledge of the way in which speech and language therapy services are organised and provided has the potential to shape the development of communication disability rehabilitation in SSA. This research has identified a range of issues requiring consideration as the profession develops and grows.